2016
DOI: 10.5505/tjtes.2016.64509
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of garlic (Allium Sativum) oil inexperimental corrosive esophageal burns

Abstract: BACKGROUND: Corrosive esophageal burns, particularly common in developing countries, lead to different problems in different age groups. The ingestion of corrosive substances can cause such problems as stricture of the esophagus, to acute perforation, and even death. Because stricture formation is related to the severity of the initial injury, the prevention of stricture constitutes a main goal of treatment. The aim of this study was to investigate the protective and anti-inflammatory effects of garlic (Allium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…As in these studies, many substances have been investigated in terms of their effects on the healing of corrosive esophagitis. Examples of these are methylene blue, polaprezinc, garlic (Allium sativum) oil, or platelet rich plasma [18][19][20][21] . The common aspect of all these substances is that they have anti-inflammatory and antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…As in these studies, many substances have been investigated in terms of their effects on the healing of corrosive esophagitis. Examples of these are methylene blue, polaprezinc, garlic (Allium sativum) oil, or platelet rich plasma [18][19][20][21] . The common aspect of all these substances is that they have anti-inflammatory and antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…birçok ilaç ve maddenin yararları gösterilmiş olsa da bunlardan klinik uygulamaya geçen olmamıştır. 38,39 Kortikosteroidler inflamasyon, granülasyon ve fibröz doku gelişimini azaltabilmektedir. Bu nedenle bazı çalışmalarda, özofagus darlığı gelişimini engellemek üzere korozif hastalar da tedavide denenmiş ve özellikle yüksek doz steroid tedavisinin evre IIb özofagus yanıklarında steroid yan etkisi olmaksızın hasarı ve özofagus dilatasyonu gereksinimini azaltabileceği gösterilmiştir.…”
Section: Korozif Madde İçimi Yönetimiunclassified
“…In their study comparing beta-aminopropionitrile (BAPN) and prednisolone, Aciksari et al [13] found that BAPN was able to decrease the development of stenosis and tissue damage better than prednisolone. Şen Tanrıkulu et al [29] found that garlic oil is an effective agent in promoting the regression of esophageal stenosis and tissue damage caused by corrosive burns. In another study, [23] investigators found that dimethyl sulfoxide may decrease the severity of tissue damage.…”
mentioning
confidence: 99%